Evaluación del estado nutricional y actividad física en estudiantes del nivel primario de la I.E. República de Venezuela, Iquitos 2025 - Alburqueque Reyna, Elvira (2025)
Malnutrition and sedentary lifestyle represent growing problems in the Peruvian school population. This study aimed to determine the relationship between nutritional status and physical activity in primary students at I.E. República de Venezuela, Iquitos 2025. A quantitative, observational, cross-sectional, correlational study evaluated 176 students from fourth to sixth grade through standardized anthropometric measurements (weight, height, BMI) and the validated PAQ-C questionnaire. Results showed combined prevalence of overweight and obesity of 30.1% (13.6% and 16.5% respectively), with obesity predominant in males (17.3%) and overweight higher in females (15.3%). Linear growth was adequate (96.6% normal height-for-age). Regarding physical activity, 82.4% showed moderate levels, 12.5% low, and 5.1% high, with critical decrease in higher grades (31.8% low PA in 6th vs. 1.7% in 4th). Gender analysis revealed differentiated patterns: girls showed higher sedentarism (13.9% vs. 11.5%) but also higher high-intensity PA (8.3% vs. 2.9%). Cross tabulation showed 31.0% of obese students had low PA, contrasting with 8.3% in normal-weight students. A moderate inverse statistically significant correlation was found between BMI and physical activity (rho=-0.413, p<0.001). The study concludes significant relationship between nutritional status and physical activity, with differentiated patterns by sex and grade, suggesting specific gender-contextualized interventions focused on upper primary grades.